2010
DOI: 10.1177/0192623310382437
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-Week Toxicity Study of Green Tea Extract in Rats and Mice

Abstract: The toxicity of green tea extract (GTE) was evaluated in 14-week gavage studies in male and female F344/NTac rats and B6C3F1 mice at doses up to 1,000 mg/kg. In the rats, no treatment-related mortality was noted. In the mice, treatment-related mortality occurred in male and female mice in the 1,000 mg/kg dose groups. The cause of early deaths was likely related to liver necrosis. Treatment-related histopathological changes were seen in both species in the liver, nose, mesenteric lymph nodes, and thymus. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 77 publications
6
54
0
1
Order By: Relevance
“…Green tea is one of the most popular beverages worldwide, and many studies have reported the safety of green tea (40)(41)(42). A previous study reported that an extraordinarily high green tea concentration is demanded to induce hepatotoxicity in rats and mice (43). In addition, stability in the blood and safety of eriodictyol, which is abundantly present in citrus fruit peels, has also been shown (44).…”
Section: Discussionmentioning
confidence: 99%
“…Green tea is one of the most popular beverages worldwide, and many studies have reported the safety of green tea (40)(41)(42). A previous study reported that an extraordinarily high green tea concentration is demanded to induce hepatotoxicity in rats and mice (43). In addition, stability in the blood and safety of eriodictyol, which is abundantly present in citrus fruit peels, has also been shown (44).…”
Section: Discussionmentioning
confidence: 99%
“…Results of experimental hepatotoxicity in animals were equivocal [221,222,223]. Chinese green tea is a popular beverage prepared from the leaves of the plant Camellia sinensis , which has been cultivated in China and other Southeast Asian countries since thousands of years [224].…”
Section: Pathogenetic Aspects Of Liver Injury From Herbal Tcmmentioning
confidence: 99%
“…Interestingly, several studies reported hepatoprotective effects of green tea preparations [53][54][55][56][57][58][59][60], whereas others demonstrated hepatotoxic effects (usually at higher concentrations) of GTE [61][62][63][64]. These conflicting data are echoed in observations in humans.…”
Section: Liver Toxicity Of Green Tea Extractmentioning
confidence: 99%